Hypothalamic food intake regulation in a cancer‐cachectic mouse model. Issue 2 (13th November 2013) - Dwarkasing, Jvalini T.; van Dijk, Miriam; Dijk, Francina J.; Boekschoten, Mark V.; Faber, Joyce; Argilès, Josep M.; Laviano, Alessandro; Müller, Michael; Witkamp, Renger F.; van Norren, Klaske
Abstract : Background: Appetite is frequently affected in cancer patients leading to anorexia and consequently insufficient food intake. In this study, we report on hypothalamic gene expression profile of a cancer‐cachectic mouse model with increased food intake. In this model, mice bearing C26 tumour have an increased food intake subsequently to the loss of body weight. We hypothesise that in this model, appetite‐regulating systems in the hypothalamus, which apparently fail in anorexia, are still able to adapt adequately to changes in energy balance. Therefore, studying changes that occur on appetite regulators in the hypothalamus might reveal targets for treatment of cancer‐induced eating disorders. By applying transcriptomics, many appetite‐regulating systems in the hypothalamus could be taken into account, providing an overview of changes that occur in the hypothalamus during tumour growth. Methods: C26‐colon adenocarcinoma cells were subcutaneously inoculated in 6 weeks old male CDF1 mice. Body weight and food intake were measured three times a week. On day 20, hypothalamus was dissected and used for transcriptomics using Affymetrix chips. Results: Food intake increased significantly in cachectic tumour‐bearing mice (TB), synchronously to the loss of body weight. Hypothalamic gene expression of orexigenic neuropeptides NPY and AgRP was higher, whereas expression of anorexigenic genes CCK and POMC were lower in TB compared to controls. In addition, serotonin and dopamine signalling pathways were found to be significantly altered in TB mice. Serotonin levels in brain showed to be lower in TB mice compared to control mice, while dopamine levels did not change. Moreover, serotonin levels inversely correlated with food intake. Conclusions: Transcriptomic analysis of the hypothalamus of cachectic TB mice with an increased food intake showed changes in NPY, AgRP and serotonin signalling. Serotonin levels in the brain showed to correlate with changes in food intake. Further research has to reveal whether targeting these systems will be a good strategy to avoid the development of cancer‐induced eating disorders. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐013‐0121‐y) contains supplementary material.